REDISTRIBUSI PAJAK MENDUKUNG PERTUMBUHAN EKONOMI - Siti Mu’awanah; Jihad Lukis Panjawa (Jurnal Ilmiah Ekonomi Dan Bisnis, 2022)
This study aims to analyze the factors that influence economic growth in Indonesia in 2000-2019. These factors are tax redistribution, inflation, exchange rate, and unemployment rate. The method used in this research is the Ordinary Least Squares (OLS) method with multiple linear regression analysis. The results showed that tax redistribution has a significant effect on economic growth, inflation has no significant, exchange rates and unemployment rate have a significant effect on economic growth